Mindfulness-acceptance-commitment program for athletes and exercisers : an action research case study - Doğan, Umut (2016)
Control-based psychological skills training (PST) practices have been widely capitalized on in sport for the past few decades, despite inconsistent empirical evidence of their efficacy on sport performance. The Mindfulness-Acceptance-Commitment (MAC) program has preliminary support as an additional approach in performance enhancement, however, there is very limited research involving its implementation especially within group settings. Current study was aimed at planning, implementation, and evaluation of a seven-session MAC program among a diverse group of active athletes and regular exercisers (n=16). This study was an educational action research case study with a mixed method design. Perspective of a novice instructor and information upon the implementation of the sessions were reflected through an elaborate narrative case description compiled based on researcher’s log and participants’ feedback. Participants also filled in the following performance and wellbeing-related scales before and after the intervention: Athlete’s Performance Self-Rating Scale (Hasker, 2010), The Acceptance and Action Questionnaire (AAQ; Hayes et al., 2004), The White Bear Suppression Inventory (WBSI; Wegner & Zanakos, 1994), and The Five Facet Mindfulness Questionnaire (FFMQ; Baer, et al., 2006). Qualitative data was analyzed through narrative and content analyses, while quantitative data was analyzed via Paired Sample t-Test. Based on the qualitative analyses, participants benefited from student centered and interactive ways of teaching (metaphors, games, videos, focus group discussions and exercises) used as part of the program. Participants also tended to prefer more active tasks like various informal mindfulness exercises as opposed to paper-based exercises. Based on the quantitative analysis, participants improved on perceived performance, thought suppression, acceptance and committed action. This study showed that it was possible for a novice instructor to adapt and apply the MAC program to a group of athletes and exercisers successfully. Future research can focus on certain sports, certain groups and include a control group and other performance-related measures, in addition to incorporating more action-oriented exercises within the program.